2011
DOI: 10.1080/14613808.2011.632084
|View full text |Cite
|
Sign up to set email alerts
|

Queering informal pedagogy: sexuality and popular music in school

Abstract: This qualitative case study explores how students' perceptions of sexual identity affect how they participate in popular music processes used in school. Seventeen high school students were invited to form five single-gendered and mixedgendered rock bands. The data collected included fieldnotes and audio recordings of observed rehearsals and individual interviews. The data were coded and analyzed from a queer theory standpoint to provide interpretations of how participants constructed their sexual identity thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…I teach popular music, and in my discipline critical pedagogy has become prized in recent years, with many citing music's transformative potential when addressing social issues owing to its embeddedness within everyday cultural practice (Abrahams, 2005;Karvelis, 2018). Notably, there has been an attentiveness to the enabling power of hip-hop (Abramo, 2011;Keyes, 2002).…”
Section: Alex De Laceymentioning
confidence: 99%
“…I teach popular music, and in my discipline critical pedagogy has become prized in recent years, with many citing music's transformative potential when addressing social issues owing to its embeddedness within everyday cultural practice (Abrahams, 2005;Karvelis, 2018). Notably, there has been an attentiveness to the enabling power of hip-hop (Abramo, 2011;Keyes, 2002).…”
Section: Alex De Laceymentioning
confidence: 99%
“…mixing, producing, songwriting, etc. ), or through the inclusion of popular music repertoire in large ensemble programs, often still taught with traditional pedagogical techniques (Abramo 2011a(Abramo , 2011bMantie 2013;Tobias 2013Tobias , 2015Tobias , 2016. In this context, progress has however been made in North America in the inclusion and introduction of music technology, recording, and producing programs as well as rock, pop, and jazz music in the curriculum (Wright 2016).…”
Section: History Of Popular Music In North American Educationmentioning
confidence: 99%
“…The majority of research in North American popular music education has focused on popular music elective courses offered to high school students (i.e. Abramo 2011aAbramo , 2011bTobias 2013Tobias , 2015. Research has suggested that while such course offerings are an important first step in introducing popular music to North American curricula, they raise questions concerning replication of issues of gender disparity (as noted by Abramo 2011aAbramo , 2011bTobias 2013Tobias , 2015Cobb 2016).…”
Section: History Of Popular Music In North American Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiculturalism and musical plurality have been the main entrances to an understanding of diversity within music education research, they have not been the only ones. Other conceptions have been related to diversity expressed as differences, for example in geographic or ethnic origin (Karlsen, 2013; Marsh, 2012; Sæther, 2008, 2010), race (Bradley, 2007; Hess, 2015), social class (Bates, 2012; Dyndahl, Karlsen, Nielsen, & Skårberg, 2014), religion (Hoffman, 2011; Jorgensen, 2011), (dis)ability (Laes & Westerlund, 2018), gender (Björck, 2011; Lamb, 2014), age (Laes, 2015) and sexuality (Abramo, 2011; Gould, 2012). As such, many of the above perspectives have been discussed by employing the perspective of social justice in music education (see, e.g.…”
Section: Introductionmentioning
confidence: 99%